Pengaruh Karakteristik Individu Dan Iklim Organisasi Terhadap Kinerja Pegawai Dengan Kepuasan Kerja Sebagai Variabel Intervening Pada Balai Latihan Kerja (BLK) Kota Padang - Ai Elis karlinda (AKADEMI PEREKAM DAN INFORMASI KESEHATAN (APIKES) IRIS PADANG, 2021)
This study aims to examine how much influence individual characteristics and organizational climate have on employee performance with job satisfaction as an intervening variable at the Padang City Training Center (BLK). The method of collecting data is through surveys and distributing questionnaires, with a sample of 86 respondents. The analytical method used is multiple linear regression analysis and path analysis using SPSS. The results obtained based on the partial test (t test) obtained that individual characteristics have a significant effect on job satisfaction. Organizational climate has no significant effect on job satisfaction. Then Individual Characteristics and Job Satisfaction have a significant effect on employee performance. Organizational climate has no significant effect on employee performance. Job satisfaction does not mediate the influence of individual characteristics on employee performance. Job Satisfaction does not mediate the effect of Organizational Climate on Employee Performance.